Fiducial displacements with improved accuracy for the global network of gravitational wave detectors. (30th November 2020) - Bhattacharjee, D; Lecoeuche, Y; Karki, S; Betzwieser, J; Bossilkov, V; Kandhasamy, S; Payne, E; Savage, R L
Abstract: As sensitivities improve and more detectors are added to the global network of gravitational wave observatories, calibration accuracy and precision are becoming increasingly important. Photon calibrators, relying on power-modulated auxiliary laser beams reflecting from suspended interferometer optics, enable continuous calibration by generating displacement fiducials proportional to the modulated laser power. Developments in the propagation of laser power calibration via transfer standards to on-line power sensors monitoring the modulated laser power have enabled generation of length fiducials with improved accuracy. Estimated uncertainties are almost a factor of two smaller than the lowest values previously reported. This is partly due to improvements in methodology that have increased confidence in the results reported. Referencing the laser power calibration standards for each observatory to a single transfer standard enables reducing relative calibration errors between elements of the detector network. Efforts within the national metrology institute community to realize improved laser power sensor calibration accuracy are ongoing.